PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MENGGUNAKAN METODE EKSPERIMEN PADA SISWA KELAS VII SMP NEGERI 1 PURBOLINGGO TAHUN PELAJARAN 2013/2014 - Endang Kurniawati; Arif Rahman Aththibby (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
The purposeofthis studyis: to describethe use ofexperimental method sin enhancingthe activity oflearning physicsclass VII students of SMPN1Purbolinggoandto describethe use ofexperimentalmethodsin improvingstudentlearning outcomesphysicsclass VII SMP N 1 Purbolinggo.This study uses a Class Action Research and 4-cycle stages: planning, action, observation and reflection for further action. The study lasted 2 cycles each cycle consisting of 2 meetings. As the subjects in this study were VII.F grade students of SMP N 1 Purbolinggo of 40 people. Means of collecting data in the form of sheets of observations and tests. From the analysis and the results of this study concluded that the use of experimental methods in the learning process can improve the activity and student learning outcomes VII.F SMP N 1 Purbolinggo on the material and temperature measurements with an average of 11.56% increase in activity. Average learning outcomes increased by 55%. Thus it can be advisable for teachers to improve the activity and student learning outcomes using experimental methods.